Measuring ploidy in interspecific Urochloa (syn. Brachiaria) using Sysmex cyflow cytometer with DAPI Cystain UV stain: Protocol for measuring ploidy in Interspecific Brachiaria fresh leaf tissue - Perea, Claudia Samantha; Hernández, Diana; Jauregui, Rosa (International Center for Tropical Agriculture, 2023)
This report presents the detailed protocol that we used for our first attempt in measuring ploidy using fresh leaf tissue in Interspecific Brachiaria using the sysmex flow cytometer with DAPI cystain UV stain. Accurate determination of ploidy is crucial for understanding the genetic characteristics of plant populations, aiding in plant breeding programs, and contributing to advancements in molecular biology. The following methodology outlines the steps for sample collection, preparation, staining, and analysis.